Factors influencing attitude toward organ and tissue donation among patients in primary clinic, Sabah, Malaysia - Kai Joo Lim; Timothy Tsin Jien Cheng; Mohammad Saffree Jeffree; Firdaus Hayati; Phee Kheng Cheah; Kuok Ong Nee; Mohd Yusof Ibrahim; Shamsul Bahari Shamsudin; Fredie Robinson; Khamisah Awang Lukman; Aza Sherin Mohd Yusuff; Dr Swe; et al. (2020)
Introduction Worldwide, the gap between organ supply and demand has widened over the years. Malaysia has one of the lowest deceased organ donation rates. Success rate of organ or tissue procurement depends on not only the approach rate by health care providers but also the awareness among the public, whereby it can be a platform for family initiation of organ donation. The purpose of this study is to assess the knowledge of and determine the factors influencing attitude toward organ and tissue donation among patients in a primary clinic.